A Pilot Study on the Efficacy of a Single Intra-Articular Administration of Triamcinolone Acetonide, Hyaluronan, and a Combination of Both for Clinical Management of Osteoarthritis in Police Working Dogs - Alves, João C.; Santos, Ana; Jorge, Patrícia; Lavrador, Catarina; Carreira, L. Miguel (Frontiers in Veterinary Science, 2020)
Objectives: To describe and compare the use and effectiveness of a single intra-articular injection (IA) of triamcinolone acetonide (TA), hyaluronan (HA), and a combination of both (TA+HA) in police working dogs with natural occurring hip osteoarthritis (OA). Study Design: Prospective, randomized, single-blinded study. Sample Population: Thirty animals with naturally occurring hip OA. Methods: Animals were randomly divided in three groups: GT, treated with 20 mg of TA per hip joint; GH, treated with treated 20 mg of HA per hip joint; and GTH, treated with a combination of 20 mg of TA and 20 mg of HA per hip joint. Response to treatment, measured by the Canine Brief Pain Inventory (divided in Pain Interference Score—PIS and Pain Severity Score—PSS) and the Hudson Visual Analog Scale (HVAS), was evaluated in seven different time points: T0 (before treatment), T1 (after 15 days), T2, T3, T4, T5, and T6 (after 1, 2, 3, 4, and 5 months, respectively). Results were compared using a Kruskal-Wallis test or a Wilcoxon signed ranks test, and p < 0.05 was set. Results: Comparing results of the different time points considered with T0, significant differences were registered in GH at T1 for HVAS (p = 0.03) and PIS (p = 0.04); and in GTH at T1 (p = 0.05 for HVAS and p < 0.05 for PIS), T2 (p < 0.04 for PIS), T3 (p < 0.03 for HVAS and p = 0.05 for PIS), T4 (p < 0.03 for HVAS and p < 0.05), and T5 (p < 0.05 for HVAS). No significant differences were found between groups when comparing scores in each time point. Individual treatment is considered successful with a reduction of ≥1 for PSS or ≥2 for PIS. In GTH, treatment was successful in four animals between T1 and T5 (40%, n = 10) and three at T6–T7 (30%, n = 10) for PSS and three animals of GTH at T1 (30%), two at T2 (20%), three between T3 and T4 (30%), and two between T5 and T7 (20%). Conclusions and Clinical Relevance: This study provides direct information on the use of these treatment modalities in patients with hip OA. Intra-articular injection with TA and HA may be a treatment option for dogs with naturally occurring OA, particularly when simultaneously used, as they provide significant improvements of PIS and HVAS scores. Individual scores improved in some animals with PIS, PSS, and HVAS.